1994
DOI: 10.1016/s0022-5347(17)35229-1
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Epidemiological Survey Using a Modified American Urological Association Symptom Index for Benign Prostatic Hyperplasia in France

Abstract: The prevalence of urinary symptoms associated with benign prostatic hyperplasia was studied in a community-based, nationwide, representative sample of 2,011 French men 50 to 80 years old. Symptoms were assessed by the American Urological Association symptom index. After exclusion of patients with prostate cancer, 6.9% of the subjects reported having undergone prostate surgery. Among the surgery-free subjects, nocturia and repeat voiding within 2 hours were the most prevalent symptoms. Based on the American Uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
2
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 11 publications
9
72
2
5
Order By: Relevance
“…In agreement with this observation, the results from a previous survey suggest that 1.14 million French men have moderate to severe LUTS suggestive of BPO. 1 Moreover, the increase of LUTS prevalence is not surprising, since the population is ageing in the developed nations and consequently more older men require treatment for LUTS. 13 The percentage of patients with speci®c co-morbidity in RCTs is not always representative for real life practice due to the fact that many patients are not included because of strict exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with this observation, the results from a previous survey suggest that 1.14 million French men have moderate to severe LUTS suggestive of BPO. 1 Moreover, the increase of LUTS prevalence is not surprising, since the population is ageing in the developed nations and consequently more older men require treatment for LUTS. 13 The percentage of patients with speci®c co-morbidity in RCTs is not always representative for real life practice due to the fact that many patients are not included because of strict exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of urinary symptoms was studied in France in 1992 in a community-based, nation-wide, representative sample of 2011 French men 50 to 80-y-old, using the I-PSS questionnaire. 1 The data revealed that 85.8% of the investigated men had mild LUTS (including 18.8% with an I-PSS score of 0), and 14.2% had moderate or severe LUTS. Based on the obtained data, the authors estimated that 1.14 million French men had moderate to severe urinary symptoms that were likely to be associated with BPO.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…6,9 The age-related increase in the frequency of urinary symptoms has been well documented. 5,8,14,15,21 Age is the major factor in changing voiding patterns. Across all ages (40±70 y old cohorts) a signi®cant increase (P`0.005) in the average AUASS, except for the 8th and 9th decades of life, is observed but with no statistically signi®cant difference.…”
Section: Series In Wisconsin Andmentioning
confidence: 99%
“…The prevalence is 36.6% in Japan according to a study by Tsukamoto 2 and 14.2% in France in a study by Sagnier. 3 Autopsies have revealed histological evidence of BPH in 90% of men older than 90 y of age. 4 As early as 1978, studies by Caine and Shapiro 5,6 demonstrated that a-blocking drugs such as phenoxybenzamine and prazosin reduced urethral resistance, thus facilitating bladder emptying.…”
Section: Introductionmentioning
confidence: 99%